Pegylated Arginine Deiminase Downregulates Colitis in Murine Models - Oz, Helieh S. (Hindawi Publishing Corporation, 2012)
Arginine deiminase (ADI), an arginine-metabolizing enzyme involved in cell signaling, is dysregulated in multiple inflammatory diseases and cancers. We hypothesized that pegylated ADI (ADI-PEG) provide protection against colitis. Methods. Dextran sodium sulfate colitis was induced in IL-10-deficient and BALB/c (WT) mice. ADI-PEG was administered i.p., and inflammatory mediators and pathology were evaluated. Results. Acute colitis in mice was manifested by increases in inflammatory biomarkers, such as serum amyloid A (SAA, P < 0.001), IL-12 p40, and disease index (3-Fold). In contrast, ADI-PEG significantly decreased clinical disease index, SAA levels, and inflammatory cytokines in blood as well as in colonic explants. Animals developed moderate (2.2 ± 0.3 WT) to severe (3.6 ± 0.5 IL-10 deficient) colonic pathology; and ADI-PEG treatment significantly improved the severity of colitis (P < 0.05). Marked infiltration of CD68(+) macrophages and iNOS expression were detected in colonic submucosa in colitic animals but not detected in ADI-PEG-treated animals. Conclusion. ADI-PEG attenuated inflammatory responses by suppression of macrophage infiltration and iNOS expression in colitic animals. ADI-PEG can serve as a potential therapeutic value in IBD.